Modelling A Customer And After Sales Services And Implementing This Model In Irarian Company - Ghandchi, Marjan Saradar (2009)
The orchestration of the after sale service department with company goals i sone of the main duties of these directors. Directors endeavour to reach this objective with the available option in this sector. But, existing resources and restrictions will not allow them to provide a full range of services. The main purpose of the research i sto present ways of prioritising defined activities in the after sale services department of a company offering electrical services in accordance with both company and customer interests.